Pengaruh Harga, Influencer Marketing Dan Live Streaming Tiktok Terhadap Keputusan Pembelian Produk Skincare Lokal Avoskin (Studi Masyarakat Kecamatan Lowokwaru Kota Malang) - Munawaroh, Salsabilatul; Rachma, N; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to find out and analyze the influence of price, influencer marketing and TikTok live streaming on the purchase decision of Avoskin's local skincare products. This study was conducted on the community of Lowokwaru sub-district, Malang city. Data collection was carried out by distributing questionnaires to 120 respondents obtained through the Hair formula, with a sample withdrawal method using purposive sampling. The results of this study show that: (1) Together, price, influencer marketing and TikTok live streamig have a significant influence on the purchase decision of Avoskin's local skincare products. (2) Price has a positive and significant effect on the purchase decision of Avoskin local skincare products. (3) Influencer marketing has a positive and significant effect on the purchase decision of Avoskin's local skincare products. (4) TikTok live streaming has a positive and significant effect on the purchase decision of Avoskin's local skincare products. Keywords: Price, Influencer Marketing, TikTok Live Streaming, Purchase Decision